EVALUASI SISTEM PENGELOLAAN LIMBAH PADAT B3 PT. INDOFARMA, TBK BEKASI - Syafrudin Syafrudin (TEKNIK, 2008)
Besides yielding product, production process also will yield discard product that we called as waste. Thetype of the waste are depended on the raw materials and other process that happened during theproduction process. As a pharmacy industry, PT. Indofarma Tbk also generate waste from their productionprocess which have potency to contaminate the environment because the most material that use for theproduction are chemicals that need to be handled seriously. The waste can be categorize as HazardousWaste and needed furthermore management to control, so it will be secure for the environment. Forpharmacy industry, the hazardous waste is in the form of the chemicals, Waste Water Treatment’s sludge,residu production process like dust from dust collector, incinerator’s fly ash, and other materials which iscame from hazardous materials.